1995
DOI: 10.1089/neu.1995.12.679
|View full text |Cite
|
Sign up to set email alerts
|

An Imaging-Based Computational and Experimental Study of Skull Fracture: Finite Element Model Development

Abstract: The development of a three-dimensional finite element model of the human skull is presented as a part of a novel imaging-based experimental and computational approach to study skull fracture. The rationale for this approach and its potential utility are presented. Mathematical model development, using computed tomography (CT) imaging data as a basis for collecting geometric characteristics of the skull, is given. The model includes anatomical detail of the cranial structure, accurate thickness distributions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…These criteria are computed using the intracranial mechanical behavior simulated by the finite element head model described in Bandak et al (1994), Takhounts et al (2003) and illustrated in Fig. 2.…”
Section: Simon Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…These criteria are computed using the intracranial mechanical behavior simulated by the finite element head model described in Bandak et al (1994), Takhounts et al (2003) and illustrated in Fig. 2.…”
Section: Simon Criteriamentioning
confidence: 99%
“…Hence, new injury criteria are proposed. In the past few decades, more than ten different three-dimensional finite element head models (FEHM) have been reported in the literature by Ward et al (1980), Shugar (1977), Hosey and Liu (1980), Dimasi et al (1991), Mendis (1992), Ruan et al (1991), Bandak et al (1994), Zhou et al (1995), Al-Bsharat et al (1999), Willinger et al (1999) and Zhang et al (2001). Fully documented head impact cases can be simulated in order to compute mechanical loading sustained by brain tissue as well as other tissues in the surrounding areas and we compare it to the real injuries described in the medical reports.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the non-invasive methods with high accuracy are urgently needed for MCD diagnosis are needed. The mathematical model based on the statistical analysis and computer technique has been used in clinic, such as computed tomography (CT) and nuclear magnetic resonance (NMR) (Bandak et al 1995;Hu et al 2011a). Levery et al established a new equation of estimated glomerular filtration rate (eGFR), named CKD-EPI, which could assess the stages of kidney diseases (CKD stage) (Levey et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Loboa and colleagues extended such approaches to address new bone and other skeletal tissue formation in distraction osteogenesis and fracture healing . The use of high‐resolution images, such as magnetic resonance imaging (MRI) and computed tomography (CT) scans, has allowed for models to more accurately depict the natural anatomical geometries of tissues . Taken together, biomechanicians showed that the kinetics of bone remodeling in response to applied forces could be predicted by computational modeling.…”
Section: Biomechanics and Computational Analysismentioning
confidence: 99%